Race and satisfaction with pain management among patients with HIV receiving long-term opioid therapy. (1st May 2021) - Ganguly, Anisha P.; Lira, Marlene C.; Lodi, Sara; Forman, Leah S.; Colasanti, Jonathan A.; Williams, Emily C.; Liebschutz, Jane M.; del Rio, Carlos; Samet, Jeffrey H.; Tsui, Judith I.
Highlights: Non-white PWH received lower doses and shorter courses of opioids than white PWH. Pain satisfaction was not significantly different among non-white and white PWH. Barriers to pain management were similar among non-white and white PWH. Abstract: Introduction: Management of chronic pain is an essential aspect of HIV primary care. Previous literature in the general population has elucidated racial disparities in the evaluation and treatment of pain. This study examined racial/ethnic differences in patient satisfaction and barriers to pain management among a cohort of PWH receiving LTOT. Materials and methods: Patient-reported survey and EMR data were compared between non-white (n = 135; 81.3 %) and white (n = 31; 18.7 %) patients in a cohort of 166 PWH receiving LTOT in two clinics in Atlanta and Boston. Quantile and linear regression were used to evaluate the association between race and pain management outcomes: 1) satisfaction with pain management (0–10) and 2) patient-related barriers to pain management, including patient perceptions of pain medications, fatalism, and communication about pain. Models were adjusted for sex, age, clinical site, and baseline general health. Results: Non-white participants were noted to receive chronic opioids for a shorter mean duration of time than white participants (6.0 versus 11.0 years, p < 0.001) and lower mean morphine equivalent daily dose (MEDD) than white participants (28.1 versus 66.9 mg, p < 0.001). In adjusted analyses, there was no significant difference in satisfaction with pain management among non-white and white participants (p = 0.101). There was no significant difference in barriers to pain management in unadjusted (p = 0.335) nor adjusted models (p = 0.397). Conclusion: While non-white PWH were noted to have received lower doses of chronic opioids and for shorter duration than white PWH, satisfaction with pain management was similar. Patient-related barriers to pain management were similar among non-white and white PWH.